MANAJEMEN PENGETAHUAN: PEMEBELAJARAN ORGANISASI DAN IMPLEMENTASI DI PERPUSTAKAAN - Muntashir (UIN Imam Bonjol Padang, 2022)
Knowledge management (KM) is an important issue in creating innovation and improving the performance of an organization. The emergence of KM brings new challenges and problems for librarians in defining information and knowledge management as the object they manage. This paper seeks to explore various ways for libraries to act as organizational learning tools while at the same time identifying ways to apply the concept of KM in library management as an organization. Literature study approach and bibliometrics are used in this study based on literature sources related to the implementation of KM in the libraries. This study found that MI is part of the KM concept that focuses on managing explicit knowledge, while overall KM manages tacit and explicit knowledge assets. In supporting the effective management of organizational knowledge assets, libraries need to expand the management role of the two forms of knowledge, so that the library can become a center for KM as well as organizational learning. Furthermore, the library as an organization can adopt the concept of KM in creating innovation and improving service quality. Digital libraries encourage KM in the management of organizational knowledge assets. The implementation of KM in the library can be applied to routine activities such as administration, strategic planning, reference services, and the use of knowledge management systems (KMS) to support collaboration in completing a particular project in libraries.